Acute Mechanical Injury to the Human Intervertebral Disc Initiates Events Implicated in Disc Degeneration. (May 2014) - Alkhatib, B. Ghalib; Rosenzweig, D.; Krock, E.; Gawri, R.; Beckman, L.; Steffen, T.; Weber, M.; Ouellet, J.; Haglund, L.
Introduction: Low back pain is a prevalent chronic disorder among individuals worldwide. Intervertebral disc degeneration is a major cause of low back pain in adults. Mechanical overload has been proposed as a potential initiating mechanism of degeneration, and previous studies have demonstrated that complex mechanical loading of lumbar motion segments can disrupt disc cell metabolism. 1 Furthermore, mechanical wedge loading of bovine caudal discs induced cell death and causes induction of catabolic genes such as IL-1β and members of the metalloproteinase and ADAMTS family of proteases which leads to loss of aggrecan. 2 The aim of this study was to investigate the effect of acute mechanical injury on cellular responses and changes in matrix composition in human intervertebral discs. Materials and Methods: Lumbar spine segments were harvested from consenting donors via the Transplant Quebec organ donation program in Montreal, Quebec. This was performed in accordance with the Institutional Review Board guidelines of the Montreal General Hospital. Discs with intact cartilaginous endplates were isolated from the lumbar spine. A single ramp compression of either 5 or 30% resulted in approximately 0.2 MPa (low noninjurious load or LNL) or approximately 1.5 MPa (acute traumatic injury or ATI) peak stress. The rate of compression was 30% strain per second. This compression protocol for acute traumatic injury consistently yields endplate fracture. Discs were, after loading, immediately put in low-serum containing media. The media was changed and collected at days 3 and 7. Proteoglycan release was evaluated in media from all culture days and in guanidium hydrochloride extracts of tissue from the loaded discs. Proteoglycan size distribution was visualized by fractionating conditioned media from low noninjurious load and acute traumatic injury samples by agarose gel electrophoresis. At day 14, disc cultures were terminated and Live/Dead analysis was performed on biopsies from seven different regions of the discs and confocal microscopy was used to quantify live and dead cells. PC12 cells, a neuronal-like cell line, were exposed to conditioned media from the cultured discs to study the potential for neurite sprouting. Nerve growth factor (NGF) levels were measured using a commercially available ELISA assay. Commercially, available cytokine arrays were used to investigate protein levels of cytokines. Disc tissue was fixed in 80% methanol and prepared for cryosectioning and histological analysis with Safranin O, hematoxylin, and Fast Green. Results: Considerable cell death was observed in discs subjected to acute traumatic injury 14 days after the load event (NP 40% viable and AF 50% viable). Discs subjected to the low noninjurious load maintained a cell viability of 85% in the NP and the AF (Fig. 1A). Investigation of GAG levels revealed that acute traumatic injury induced a considerable release of GAG from the tissue as compared with low noninjurious load samples (Fig. 1B). This was confirmed by histological analysis where a loss of Safranin O staining was apparent in the tissue of discs subjected to acute traumatic injury. Fractionation of the conditioned media by agarose gel electrophoresis revealed a wider size distribution of the proteoglycans released from the discs after acute traumatic injury as compared with the discs subjected to low noninjurious load. Elevated levels of inflammatory cytokines and pain mediators were detected in the culture media from discs subjected to acute traumatic injury group compared with discs subjected to low noninjurious load. Furthermore, conditioned media from the acute traumatic injury disc cultures caused significantly more neurite outgrowth in PC12 cells compared with disc cultures from discs subjected to low noninjurious load. Conclusion: Cell death and cytokine production combined with loss of GAG indicate that acute mechanical injury initiated degradative processes that could lead to disc degeneration. A wider size distribution of proteoglycans in conditioned media from discs subjected to acute traumatic injury further confirmed that this type of load induced expression and/or activation of proteases in the disc. Acute injury also stimulated the remaining viable cells to produce elevated levels of inflammatory cytokines. Once the proteoglycan content in the matrix has been degraded, elevated levels of NGF could lead to neuronal in-growth and directly cause pain. Further investigation may yield insights to novel diagnostics and therapies for degenerative disc disease. Disclosure of Interest None declared References Adams MA, Freeman BJ, Morrison HP, Nelson IW, Dolan P. Mechanical initiation of intervertebral disc degeneration. Spine 2PO.004;25(13):1625–1636 Walter BA, Korecki CL, Purmessur D, Roughley PJ, Michalek AJ, Iatridis JC. Complex loading affects intervertebral disc mechanics and biology. Osteoarthritis Cartilage 2011;19(8):1011–1018